2019
DOI: 10.3390/nu11092177
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Type 2 Diabetes

Abstract: This editorial aims to examine the risk factors associated with type 2 diabetes and to discuss the evidence relating to dietary strategies for managing people with this condition. It is clear from the evidence presented that a range of dietary interventions can provide useful approaches for managing people with type 2 diabetes, including the regulation of blood glucose and lipid parameters, and for reducing the risks of acute and chronic diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 26 publications
1
37
1
4
Order By: Relevance
“…T2DM development depends on various genetic, environmental, socioeconomic, and lifestyle factors [ 39 ]. Genetic charge plays a vital role in this disease, thus, individuals with diabetic first-degree relatives are four to six times more likely to develop T2DM.…”
Section: Type-2 Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…T2DM development depends on various genetic, environmental, socioeconomic, and lifestyle factors [ 39 ]. Genetic charge plays a vital role in this disease, thus, individuals with diabetic first-degree relatives are four to six times more likely to develop T2DM.…”
Section: Type-2 Diabetes Mellitusmentioning
confidence: 99%
“…Diet quality and a healthy lifestyle are recommended for the prevention of most chronic degenerative diseases. As already mentioned, T2DM is a metabolic condition characterized by chronic hyperglycemia and results from the interplay of nutritional, environmental, and genetic factors [ 39 ]. The role of dietary energy, macronutrients, micronutrients, and bioactive compounds in developing T2DM have been widely studied [ 80 , 81 ].…”
Section: Algal Composition Structure and Beneficial Effects On Type-2 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, our study showed that total energy intake was not correlated with glycemic variability in T1DM patients after adjusting for the potential confounders. A large number of studies have provided evidence for the relationship between energy intake and glycemic control in the diabetic population [20][21][22][23], in which caloric restriction had beneficial effects on blood glucose control [24,25]. A previous study also explored the relationship between meal timing, meal frequency, breakfast consumption habits, and glycemic control (HbA1c) in T1DM patients, who were enrolled in the Finnish Diabetic Nephropathy Study [26].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação às concentrações eritrocitárias verifica-se que 50,77% apresentam indicativo de deficiência de selênio e 46,15% e 80,3% apresentam indicativo de excesso de zinco e manganês. A prevalência desta doença tem aumentado no mundo, em parte devido às mudanças do estilo de vida que predispõe os indivíduos à obesidade e sobrepeso (OJO, 2019). Neste presente estudo verificou-se que 90% dos pacientes apresentavam peso acima do adequado, sendo 43% sobrepeso e 47% obeso.…”
Section: Análise Estatísticaunclassified